TEKNIK PENGAMBILAN CITRA BIBIT IKAN BANDENG MENGGUNAKAN AVAILABLE - Sinukun, Ruly Sutrisno; Pakaya, Roys (Universitas Muhammadiyah Gorontalo, 2023)
The technology that is currently being developed is digital image technology or what is commonly called image processing. This science is a science that talks a lot about image management. And not infrequently penetrated into the world of agriculture and fisheries. One example of image processing research is the one conducted by Indrabayu 2016 with the title milkfish freshness detection system using imagery. And the research I did in 2014 with the title Identification of the Number of Nener Images Using the Blob Method which I proceeded at SNATS Yogyakarta. In both the calculation of milkfish seedlings or research that discusses the freshness detection of milkfish, the two studies did not escape the so-called supporting data or what is commonly called datasets. This supporting data when not paying attention to good retrieval techniques will greatly affect the results of the study. The less noise or interference that exists in the image, the better results will be.